Orthodontic Treatment of a Case with Maxillary Impacted Canines and Congenitally Missing First Premolars - Sabri İlhan Ramoğlu; Zehra İleri; Yaşar Bedii Göyenç (Galenos Yayinevi, 2009)
Depending on their roles in oral functions and smile and face esthetic, impaction of maxillary canines is an important problem that should be treated by a conservative approach. In this case report, orthodontic treatment of a patient (9-year 5- months) with congenitally missing one maxillary premolar on both side and impacted two maxillary canines were introduced. The canines were impacted in different depth and angulations; right canine was almost parallel to occlusal plane. Following the determination of the teeth were not erupting by a panoramic radiograph taken in the sixth month after first application, patient was accepted to fixed orthodontic therapy. Primary canines were extracted. Rotations of upper premolars and molars were corrected and spaces were organized. However no traction was applied to maxillary canines, it was determined that they were erupting in the following panoramic radiograph. When they are fully erupted they were bonded. The treatment finished in three years and seven months time. This case shows the importance of early diagnose of impacted maxillary canines and their ability to erupt by uprighting when their spaces are prepared.